The Activity of Social and Psychological Rehabilitation Centres for Families in Ivano-Frankivsk Region (Ukraine) - Victoriia Stynska; Oksana Tytun (Vasyl Stefanyk Precarpathian National University, 2018)
The article deals with the work of social and psychological services in Ivano-Frankivsk region (Regional Center of social and psychological help in the village Verkhovyna, district Verkhovyna, Municipal social rehabilitation center of mother and child "Mistechko myloserdia sviatogo Mykolaia", Interregional center of social and psychological rehabilitation of children in the village Medynia, district Galytskyi). The centers aim at implementation of new forms of social support of women, prevention of abandonment and child's social orphanhood, providing social, psychological, pedagogical, medical and legal assistance. The centers carry out the activity on principles of human rights protection, humanity, legitimacy, availability, mutual respect and confidentiality. It has been found that the centers aim at: social and psychological diagnostics; psychological and pedagogical help, social and medical care; correction-developing work; adaptation to family environment and legal assistance. It was concluded that centers of social and psychological rehabilitation of families in Ivano-Frankivsk region due to the wide range of tasks have become special places (schools) of pedagogical, psychological and medical help to the children, young people and families with children in difficult life situations.